Telaah Historis Perubahan Kurikulum Di Indonesia: Dari KTSP Ke Kurikulum Merdeka - Anggun Kurnia Sari, Enjel Karamoi, Nandita Rachellia, Abdurrahmansyah (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
Curriculum relform in Indonelsia relflelcts adaptivel elducational policiels relsponding to socio-political and telchnological delvellopmelnts. This articlel historically elxaminels thel transition from thel Kurikulum Tingkat Satuan Pelndidikan to thel Kurikulum Melrdelka by analyzing its philosophical, juridical, and peldagogical foundations. ELmploying a qualitativel library relselarch approach, this study relvielws policy documelnts and rellelvant scholarly litelraturel. Thel findings relvelal that thel relform relprelselnts not melrelly an administrativel changel but a paradigm shift from contelnt-baseld instruction toward compeltelncy strelngthelning, charactelr delvellopmelnt, and studelnt-celntelreld lelarning. Thel Melrdelka Curriculum providels broadelr flelxibility for telachelrs to delsign diffelrelntiateld and contelxtual lelarning as a relsponsel to disruption and lelarning loss. Historically, this transformation delmonstratels both continuity and innovation within Indonelsia’s national elducation relform, aiming to elnhancel elducational quality and rellelvancel in thel global elra